Molecular testing in evaluating thyroid nodules (Bangladesh Journal of Otorhinolaryngology, 2026)
The high prevalence of thyroid nodules are due to increased availability of neck ultrasound . FNAC plays a central role to see benign and malignant nodules. About 20% of FNAC results come back as indeterminate nodule (Thy 3A/3F,Thy 4) for which diagnostic hemithyroidectomy or total thyroidectomy is done but ony 10-30% cases ultimately come back as malignant nodules after biopsy leading to unnecessary operation of 70% cases. In these context the recent availability of molecular tests has helped to supplement malignancy risk assessment in lieu of proceeding directly with a strategy of either surveillance or diagnostic surgery.This paper aims to review and compare three main commercially available molecular cytology platforms using in Europe, and USA, Afirma GSC, Thyroseq GC, and ThyGeNEXT + ThyraMIR. Between these tests, with considerations for factors such as cost and processing time. Thyroseq GC  is most commonly used provides detailed genomic information and specific management recommendations. ThyGeNEXT + ThyraMIR, though less studied, presents promising results, particularly in miRNA analysis for weak driver mutations. While molecular testing has primarily served diagnostic purposes, advancements in understanding genetic alterations now offer therapeutic implications.Bangladesh J Otorhinolaryngol 2026; 32(1): 39-44